Azadirachta indica A. Juss Ameliorates Mouse Hepatitis Virus-Induced Neuroinflammatory Demyelination by Modulating Cell-to-Cell Fusion in an Experimental Animal Model of Multiple Sclerosis - Sarkar, Lucky; Putchala, Ravi Kiran; Safiriyu, Abass Alao; Das Sarma, Jayasri (Frontiers in Cellular Neuroscience, 2020)
Mouse hepatitis virus (MHV)-induced murine neuroinflammation serves as a model to study acute meningoencephalomyelitis, hepatitis, and chronic neuroinflammatory demyelination; mimicking certain pathologies of human neurological disease, Multiple Sclerosis. MHV-induced acute neuroinflammation occurs due to direct glial cell dystrophy instigated by CNS-resident microglia and astrocytes; rather than peripheral CD4+T cells-mediated myelin damage prevalent in EAE. Viral envelope Spike glycoprotein-mediated cell-to-cell fusion is an essential mechanistic step for MHV-induced CNS pathogenicity. Though Azadirachta indica (Neem), a traditional phytomedicine is known for its anti-inflammatory, anti-fungal, spermicidal activities, not much is known about anti-neuroinflammatory properties of its bark (NBE) in MHV-induced acute neuroinflammation and chronic demyelination. Recombinant demyelinating MHV strain (RSA59) was preincubated with NBE to arrest the infection-initiation event and its effect on viral replication, viral transcription, cytokines expression, and successive pathogenicity were investigated in vitro and in vivo. Virus-free Luciferase assay explained NBE’s anti-cell-to-cell fusion activity in vitro. Intracranial inoculation of RSA59 preincubated with NBE into mouse brain significantly reduces acute hepatitis, meningoencephalomyelitis, and chronic progressive demyelination. Besides, NBE effectively restricts viral entry, dissemination in CNS, viral replication, transcription, viral Nucleocapsid and inflammatory cytokines expression. Conclusively, A. indica suppresses MHV-induced neuroinflammation and neuropathogenesis by inhibiting cell-to-cell fusion and viral replication. From mechanistic standpoints, NBE may directly bind to the virus-host attachment Spike glycoprotein, known to play major role in viral entry, viral assembly, and cell-to-cell fusion as a mode of viral dissemination. Further studies will focus on combining bioanalytical assays to isolate potential NBE bioactive compound(s), contributing towards the said anti-viral activity.